2015
DOI: 10.1002/cctc.201402871
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of a Hexagonal‐Shaped NiO Nanocatalyst with Highly Reactive Facets {1 1 0} and Its Catalytic Activity

Abstract: A new facile chemical approach has been developed to produce hexagonal‐shaped NiO nanocrystals with high‐energy facets {1 1 0} under hydrothermal synthesis followed by annealing in the presence of air. The phase purity, crystallinity, shape/size, and mesostructure of NiO nanocrystals were investigated by powder XRD and high‐resolution transmission electron microscopy. The size, shape, and exposed crystal facets of the nanocrystals are the key factor for their physical and chemical properties. Herein, the chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 65 publications
3
15
0
Order By: Relevance
“…Different from the NiO nanoparticles, the AC-NiO nanotablets revealed three additional Raman peaks at 1360, 1586, and 2856 cm -1 , attributing to D, G, and 2D bands of AC nanosponges Figure 4a shows the crystallographic properties of the NiO nanoparticles and the AC-NiO nanotablets. In XRD patterns, both the NiO nanoparticles and the AC-NiO nanotablets exhibited the diffraction peaks of 37.2, 43.2, 62.9, 75.4, and 79.3° from (111), ( 200), ( 220), (311), and (222) crystal planes of cubic NiO (JCPDS card no: 04-0835), respectively [55,56]. The only one thing different from each other was that the AC-NiO composites include an additional peak at 26.5°, arising from the (002) phase of AC [45][46][47] (see also Figure S2).…”
Section: Morphological and Structural Properties Of Nio And Ac-niomentioning
confidence: 99%
“…Different from the NiO nanoparticles, the AC-NiO nanotablets revealed three additional Raman peaks at 1360, 1586, and 2856 cm -1 , attributing to D, G, and 2D bands of AC nanosponges Figure 4a shows the crystallographic properties of the NiO nanoparticles and the AC-NiO nanotablets. In XRD patterns, both the NiO nanoparticles and the AC-NiO nanotablets exhibited the diffraction peaks of 37.2, 43.2, 62.9, 75.4, and 79.3° from (111), ( 200), ( 220), (311), and (222) crystal planes of cubic NiO (JCPDS card no: 04-0835), respectively [55,56]. The only one thing different from each other was that the AC-NiO composites include an additional peak at 26.5°, arising from the (002) phase of AC [45][46][47] (see also Figure S2).…”
Section: Morphological and Structural Properties Of Nio And Ac-niomentioning
confidence: 99%
“…The XRD patterns of NiO, CuFe 2 O 4 , and NiO/OA‐CuFe 2 O 4 compounds are shown in Figure . The pattern of NiO reveals a crystalline structure with peaks appearing at 37.2, 43.2, 62.8, 75.3, and 79.3°, corresponding to (111), (200), (220), (311), and (222) planes of face‐centered cubic structure of NiO, respectively (JCPDS 00–078‐0429, Figure a) . Furthermore, the diffraction peaks observed at 16.9, 31.3, 32.0, 36.3, 37.90, 39.2, 43.2, 56.8, and 62.8°correspond to (111), (220), (221), (311), (222), (202), (331), (511), and (440) planes of cubic structure of CuFe 2 O 4 , respectively (JCPDS 00–020‐0781, Figure b) .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, an increasing number of research communications, articles and reviews are being reported every day. The work performed by Jaroniec et al., Stucky et al., Antonelli et al., Bhaumik et al., Zhao et al., and Ryoo et al . are worth mentioning here.…”
Section: Introductionmentioning
confidence: 81%
“…Mesoporous silica can act as an excellent support for doping of numerous transition and non‐transition heteroelements because a great variety of structures can be obtained owing to the reasonable flexibility of the tetra‐coordinated silicon atoms and precise control of the hydrolysis‐condensation reactions that result in a lower reactivity and higher thermal stability of the amorphous networks, good ability to stabilize different heteroatoms into the frameworks, and strong grafting ability towards various organic functional groups . As a result of the multiple applications in the field of nanoscience and nanotechnology, a number of metal incorporated silica‐based mesoporous materials, such as Ti‐MCM‐41, Mn‐loaded Ti‐SBA‐15, Zn‐doped silica, CeO 2 ‐silica, Mn‐doped ceria–silica, Fe 3 O 4 nanoparticles doped SBA‐15, Pd grafted silica, CoO‐SBA‐15, and many more, have been reported in the literature.…”
Section: Synthesis Strategies For Different Mesostructured Ceria–silmentioning
confidence: 99%